KUALITAS PENGALAMAN DALAM MEMODERASI GAYA HIDUP, KESADARAN MEREK DAN KUALITAS PRODUK TERHADAP MINAT BELI ULANG AIR MINUM LE MINERALE - Fadhila Rizqa Zhafira; Visca Chairunisa; Rygo Aliamin; Natasya Fadrika Dewi; Agustini Tanjung (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2024)
This study aims to determine the effect of lifestyle, brand awareness, and The purpose of this study is to determine the effect of lifestyle, brand awareness, and product quality on consumer repurchase intentions for bottled water products with the Le Minerale brand, and to evaluate the quality of experience as a moderating variable used to weaken or strengthen it. The research method used is a quantitative method in which the object of this research is the people who consume Le Minerale brand mineral water products in the Bekasi Regency area. The size of the respondents taken was purposive sampling, so conditionally it indicated that the required respondent is 70 samples. The data collected was processed using a linear regression test technique, namely the SmartPLS 3.0 application. The conclusions resulting from this study: 1) Le Minerale brand mineral water customers who make purchases feel in accordance with the behavior and a healthy consumptive lifestyle so that they can encourage consumers to do repurchase intention 2) Brand awareness can encourage customer repurchase intentions, because the deeper the customer recognizing Le Minerale Brand Minerale brand mineral waterproducts, the higher the motivation for consumer interest to carry out repurchase intention activities 3) Le Minerale brand mineral water products are guaranteed benefits and freshness, to encourage customer interest to do repurchase intentions 4) Experience quality has role as a predictor moderating variable, so that it cannot moderate lifestyle towards repurchase intention of Le Minerale branded mineral water 5) Quality of experience is able to moderate brand awareness towards repurchase intention of Le Minerale branded drinking water products 6) Quality of experience has a role as a moderating predictor, so the impact on product quality towards repurchase intention cannot be considered.